German merchants’ distress over “the torments of flax”: a new approach to the composition and genesis of Gr vocabulary - Lemeškin, Ilja (Baltistica, 2018)
It is reasonable to analyse the medieval Baltic lexicography represented by the Elbing German-Old Prussian vocabulary and the so-called S. Grunau‘s vocabulary through the prism of the Hanseatic language policy and in the context of the bilingual and utilitarian Hanseatic lexicographic production. The chosen angle of analysis reveals the similarity of the structure of the closely related vocabularies. A very close relationship can be seen between the conversations of Russian Books and the lexicographic work included in the Prussian Chronicle by S. Grunau. The article suggests a conjecture which corrects an error that emerged during the copying of the manuscript. Because of the conjecture the lexicographic work becomes transparent and logical.
Keywords: Old Prussian; Hanseatic lexicography; the lexicographic source used by S. Grunau; a small Prussian Book; conversations; conjecture